The Correlation between Age and Work Stress in Ship Crew at Tumumpa Beach Fisheries Port, Manado City - Rivald Semuel Jacobs; Oksfriani Jufri Sumampouw; Ester Candrawati Musa (Yayasan Adra Karima Hubbi, 2025)
Background. Work stress is the main indication that results in physical, mental and behavioral disruption of everyone, this is due to the inability of individuals to cope with stressors. Ship crew members are a vulnerable job and are at risk of work stress. Age is one of the triggering factors for work stress which as you get older, it will increase the risk of work stress. Purpose. The purpose of this study is to measure the relationship between age and work stress in the crew of the ship at the Tumumpa Beach Fisheries Port, Manado City. Method. This is an observational research with a cross sectional approach. This research was carried out at the Tumumpa Beach Fisheries Port in July-November 2023. The number of samples used in this study was 156 respondents. The variables of this study are divided into 2, namely age and work stress. Primary data collection was obtained directly from the distribution of questionnaires using the self-administered questionnaire method. Data analysis was carried out univariate and bivariate. Results. The results showed that the age of the respondents ranged from 17-64 years with an average age of 36.22 years. The results of this study show that the work stress score is in the interval of 90-119. The average work stress score was 107.23. In addition, the most respondents were distributed in the Medium category with 114 respondents (73.1%). The results of the analysis based on the Pearson Correlation test obtained a significance value of 0.311. This value shows that there is no significant relationship between age and work stress. Conclusion. It can be concluded that age is not related to work stress in crew members at Tumumpa Beach Fisheries Port, Manado City. Further analysis can be carried out in the next research to measure which variables are the factors causing work stress in crew members so that it can be the basis for policies for work stress control in crew members.